Mechanisms of endometrial aging: lessons from natural conceptions and assisted reproductive technology cycles - Chemerinski, Anat; Garcia de Paredes, Jessica; Blackledge, Kristin; Douglas, Nataki C.; Morelli, Sara S. (Frontiers in Physiology, 2024)
Until recently, the study of age-related decline in fertility has focused primarily on the ovary; depletion of the finite pool of oocytes and increases in meiotic errors leading to oocyte aneuploidy are well-established mechanisms by which fertility declines with advancing age. Comparatively little is known about the impact of age on endometrial function. The endometrium is a complex tissue comprised of many cell types, including epithelial, stromal, vascular, immune and stem cells. The capacity of this tissue for rapid, cyclic regeneration is unique to this tissue, undergoing repeated cycles of growth and shedding (in the absence of an embryo) in response to ovarian hormones. Furthermore, the endometrium has been shown to be capable of supporting pregnancies beyond the established boundaries of the reproductive lifespan. Despite its longevity, molecular studies have established age-related changes in individual cell populations within the endometrium. Human clinical studies have attempted to isolate the effect of aging on the endometrium by analyzing pregnancies conceived with euploid, high quality embryos. In this review, we explore the existing literature on endometrial aging and its impact on pregnancy outcomes. We begin with an overview of the principles of endometrial physiology and function. We then explore the mechanisms behind endometrial aging in its individual cellular compartments. Finally, we highlight lessons about endometrial aging gleaned from rodent and human clinical studies and propose opportunities for future study to better understand the contribution of the endometrium to age-related decline in fertility.